American little magazines of the Fin de Siécle : art, protest, and cultural transformation - MacLeod, Kirsten, 1969- (Studies in book and print culture., 2018)
"In American Little Magazines of the Fin de Siecle, Kirsten MacLeod examines the rise of a new print media form--the little magazine--and its relationship to the transformation of American cultural life at the turn of the twentieth century. Though the little magazine has long been regarded as the preserve of modernist avant-gardes and elite artistic coteries, for whom it served as a form of resistance to mass media, MacLeod's detailed study of its origins paints a different picture. Combining cultural, textual, literary, and media studies criticism, MacLeod demonstrates how the little magazine was deeply connected to the artistic, social, political, and cultural interests of a rising professional-managerial class. She offers a richly contextualized analysis of the little magazine's position in the broader media landscape: namely, its relationship to old and new media, including pre-industrial print forms, newspapers, mass-market magazines, fine press books, and posters. MacLeod's study challenges conventional understandings of the little magazine as a genre and emphasizes the power of "little" media in a mass-market context."--